Adubação dos Capins Jiggs e Hemárthria em Neossolo Quartzarênico no Ecótono Cerrado-Amazônia. - Oliveira, Hugo Mariano Rodrigues de (Universidade Federal do Tocantins, 2023)
The objective was to evaluate the effect of chemical and organic fertilizers and their combination in grasses Cynodon dactylon cv Jiggs and HemarthriaAltissima cv. Floratalthe work was performed in the experimental area in the School of Veterinary Medicine and Zootechny (EMVZ) of the Federal University of Tocantins (UFT), Araguaína, TO. The experiment was a factorial arrangement 2x4, with three replications. The treatments consisted of two grasses (Jiggs, limpograssFloralta) and four fertilizer types (without fertilization - SA; organic fertilizer - O; chemical fertilization - Q, chemical fertilizer with organic - Q + O). The variables evaluated were: height; percentage and production of leaf, stem and dead material; leaf: stem ratio; dry matter production and full green mass; bulk density. The limpograss grass showed higher height, percentage of stem, PMS and thatched production compared to Jiggs which in turn had higher proportion of leaf, dead material and relationship F: C. The interaction between grass fertilizer x occurred only for percentage of MM. In the evaluation for the type of fertilizer was the most productive Q + O followed by Q and What is not different this same sequence was observed for percentage of leaf. There was no significant effect for the type of grass (P> 0.41) and used fertilizer (P <0.13) in the variable bulk density. The Hemarthria grass had increased production of dry matter, green matter and stem relative to Jiggs. The highest yield of grasses was with joint application of chemical and organic fertilizers.